Reprogramming of Adult Retinal Müller Glial Cells into Human-Induced Pluripotent Stem Cells as an Efficient Source of Retinal Cells - Amélie Slembrouck-Brec; Amélie Rodrigues; Oriane Rabesandratana; Giuliana Gagliardi; Céline Nanteau; Stéphane Fouquet; Gilles Thuret; Sacha Reichman; Gael Orieux; Olivier Goureau (Stem Cells International)
The reprogramming of human somatic cells to induced pluripotent stem cells (iPSCs) has broad applications in regenerative medicine. The generation of self-organized retinal structures from these iPSCs offers the opportunity to study retinal development and model-specific retinal disease with patient-specific iPSCs and provides the basis for cell replacement strategies. In this study, we demonstrated that the major type of glial cells of the human retina, Müller cells, can be reprogrammed into iPSCs that acquire classical signature of pluripotent stem cells. These Müller glial cell-derived iPSCs were able to differentiate toward retinal fate and generate concomitantly retinal pigmented epithelial cells and self-forming retinal organoid structures containing retinal progenitor cells. Retinal organoids recapitulated retinal neurogenesis with differentiation of retinal progenitor cells into all retinal cell types in a sequential overlapping order. With a modified retinal maturation protocol characterized by the presence of serum and high glucose levels, our study revealed that the retinal organoids contained pseudolaminated neural retina with important features reminiscent of mature photoreceptors, both rod and cone subtypes. This advanced maturation of photoreceptors not only supports the possibility to use 3D retinal organoids for studying photoreceptor development but also offers a novel opportunity for disease modeling, particularly for inherited retinal diseases.